Areas of endemism in the southern central Andes - Aagesen, Lone (2012)
This paper analyzes the distribution of vascular plants species endemic to the southern central Andes (south-western Bolivia and north-western Argentina). All 540 species endemic to the study regions (approx. 720600 km2 ) have been included in the analysis. The main part of the endemic species is found in semiarid habitats between 1500-3500 m asl pointing to the topographically complex plateau, slope, and valley system of the southern central Andes as the main locations for its endemic flora. The distribution of the endemic species within arid sites is in contrast with that of vascular plant diversity in general, as the most diverse habitat of the region is the moist subtropical Tucumano-Bolivian Yungas forest of the eastern Andes slope. A total of 17 well defined and partly overlapping distribution patterns were indentified. The broadest distribution pattern defines a general area of endemism for the southern central Andes. This area extends through nearly the entire region and is defined by species that are widespread within the region in desert to sub-humid environments of the high Andes, slopes, or valleys. Nearly all other areas of endemism are nested within this broad distribution pattern as successively north-south overlapping areas along the slopes and valleys of the Andes and the Pampeanas Range. Despite the distributional bias of endemism towards the arid sites almost half of the endemic species are restricted to a few high endemic areas that lie in juxtaposition to the main rainfall zones. These areas contain the widest habitat ranges in terms of altitude and rainfall within the region with the endemic species being equally variable in altitude and moisture requirements. Previous defined phytogeographic units were not recognized among the distribution patterns. However, the northern part of the Prepuna can be defined as two partly overlapping distribution patterns.